قياس مستوى جودة الحياة الوظيفية لدى موظفي شبه طبي مستشفى ببومرداس - سلام, سليمة (جامعة الوادي - University of Eloued, 2022)
تهدف هذه الدراسة إلى قياس مستوى جودة الحياة الوظيفية لدى موظفي شبه الطبي مستشفى ببومرداس، و شملت الدراسة عينة من موظفي شبه طبي بمستشفى بومرداس، و توصل البحث إلى أن جودة الحياة الوظيفية في المستشفى ذات مستوى المتوسط، و من نتائج البحث أيضا أن فعالية برامج جودة الحياة الوظيفية و تحسينها و تطويرها يرتكز على وجود نظام اتصالات فعال و مفتوح بين الموظفين و المؤسسة و الجهة الوصية أي وزارة الصحة. This study aims to measure the level of quality of functional life of paramedical staff in Boumerdes Hospital, and the study included a sample of paramedical staff in Boumerdes Hospital, and the research reached a set of results, the most important of which is that the quality of career in the hospital is of an average level, and from the results of the research Also, the effectiveness, improvement and development of career quality programs is based on the existence of an effective and open communication system between employees, the institution and the Ministry of Health
Measuring the level of quality of work life for paramedical employees A case study of a hospital in Boumerdes
مقال
Keywords: جودة الحياة الوظيفية ; قياس جودة الحياة الوظيفية؛ ; مستشفى ببومرداس.; quality of work life; measuring the quality of work life ; Boumerdes Hospital